Continuous professional development: An overview from English language teachers in east Kalimantan - Abdul Halim; Yih-Sheue Lin; Mustofa Mustofa; Khusnul Khatimah (Universitas Bengkulu, 2022)
The purpose of the study was to explore how continuous professional development is conducted, who conducts it, and the factors that influence it. According to the laws of the Republic of Indonesia, teaching is a professional job that requires certain educational and training qualifications so that teachers can become professional personnel. By seeing the importance of professionalism in this work and in order to see the picture of the CPD of teachers in East Kalimantan, this research is important to carry out. This research uses a qualitative case study method. The subjects of this study were teachers (n=10) from ten schools in Samarinda, Kutai Kartanegara, and Balikpapan. Data were collected using a CPD questionnaire and interviews. The data obtained were analysed and presented with descriptions and tables or charts. The data indicated that most of the teachers participated in the study are aware of the components of professional teacher indicated from the government laws. The study also reveals how the CPD is conducted by different stakeholders. Some suggestions are proposed based on the results of the study.